2018
DOI: 10.3390/ijms19030784
|View full text |Cite
|
Sign up to set email alerts
|

The Inside Story of Adenosine

Abstract: Several physiological functions of adenosine (Ado) appear to be mediated by four G protein-coupled Ado receptors. Ado is produced extracellularly from the catabolism of the excreted ATP, or intracellularly from AMP, and then released through its transporter. High level of intracellular Ado occurs only at low energy charge, as an intermediate of ATP breakdown, leading to hypoxanthine production. AMP, the direct precursor of Ado, is now considered as an important stress signal inside cell triggering metabolic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 85 publications
(104 reference statements)
2
39
0
1
Order By: Relevance
“…It has been reported that intracellular adenosine could be converted to other metabolites, including AMP and inosine. Adenosine could be phosphorylated to AMP by the activity of adenosine kinase, or it could be converted to inosine by the activity of adenosine deaminase as mentioned previously [41]. Accordingly, the potential metabolic change of adenosine in adenosine-mediated CCA cell suppression was elucidated.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…It has been reported that intracellular adenosine could be converted to other metabolites, including AMP and inosine. Adenosine could be phosphorylated to AMP by the activity of adenosine kinase, or it could be converted to inosine by the activity of adenosine deaminase as mentioned previously [41]. Accordingly, the potential metabolic change of adenosine in adenosine-mediated CCA cell suppression was elucidated.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, we further investigated the possible metabolic phases of adenosine once it was transported into CCA cells. In normal cells, intracellular adenosine could be converted to AMP by the activity of adenosine kinase to regenerate the energy carrier molecules (ADP and ATP, subsequently) and to serve as a precursor for nucleotide synthesis [41]. On the other hand, adenosine could also be deaminated by adenosine deaminase to inosine, which can also be used as another precursor in nucleotide synthesis [41].…”
Section: A Conversion Of Adenosine To Amp Is Required For the Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracellular adenosine is considered a retaliatory metabolite in a protective feedback control pathway in response to excessive intracellular ATP consumption (Newby 1984). Intracellular AMP and adenosine rise when ATP is depleted in low energy states and function as metabolic stress signals, leading to activation of non-AR-dependent mechanisms such as AMP-dependent protein kinase (AMPK) (Camici et al, 2018) and, indirectly, to AR activation by extracellular adenosine. Extracellular adenosine can also be produced locally during injury or an inflammatory response (Haskó et al, 2008).…”
Section: Endogenous Adenosinementioning
confidence: 99%
“…Adenosine is of great importance to ensure the regulation of homeostasis and maintenance of vascular tonus [34]. Higher concentrations of adenosine may also be considered as a stressful condition and the signal causes adenosine phosphorylation to AMP by the low KM of adenosine kinase, consequently increasing the activity of ecto-5 '-nucleotidase [35], reinforcing the feedback regulation.…”
Section: Cl-adenosine (Ado) Significantly Increased the Amp Hydrolysimentioning
confidence: 99%